Evaluating the Quality Assurance and Control of Hot-Mix Asphalt from Selected Plants in South West, Nigeria - A. O. Olutaiwo; Adewale Olutaiwo (Nigerian Journal of Technological Development, 2020)
Roads are essential necessity of every nation and it is possible that even with proper designs, the roads might not be constructed to the design standard due to poor quality assurance and control resulting in poor pavement quality. This study presents experimental results carried out on various hot - mix asphalt (HMA) samples obtained across different Asphalt plants in South West Nigeria. This was done to determine the extent to which the HMA used in the construction and rehabilitation of Nigerian roads affect their service life. Six samples of the asphalt binder (bitumen) were obtained from each plant over a period of six months and tested. The tested properties were assessed based on the level of conformance with the specifications and requirements from the FMWH General Specification (Roads and Bridges). The results revealed that HMA from plant B had a specific gravity of 1.01, penetration of 65.00 mm, softening point of 53 oC, flash point of 237.00 oC, peak Marshall Stability of 18.25 kN, flow of 3.87 mm and voids in total mixture peak value of 5.08 %. HMA from plant E had a specific gravity of 1.03, penetration of 65.00 mm, softening point of 51 oC, flash point of 239.00 oC, peak marshall stability of 18.26 kN, flow of 3.67 mm and voids in total mixture peak value of 4.99 % and these were adjudged the best in conformance with the FMWH specifications. Adequate monitoring of HMA quality for either binder or wearing courses by carrying out quality control and assurance tests is thereby recommended as it affects pavement durability and performance.